6 - Globalisation, Decoloniality and the Question of Knowledge Production in Africa: A Critical Discourse - Afolabi, Olugbemiga Samuel (Journal of Higher Education in Africa, 2022)
Globalisation entails the process of production and exchange at the planetary level, making the world a global village. At global epistemic levels, it has been dominated by Eurocentrism and Western knowledge production paradigms and platforms. Characterised by asymmetrical and superior- inferior relationships between the global North generally and global South, in Africa in particular, virtually all facets of knowledge production, utilisation and transfer have been dominated by the West. In Africa, the process of knowledge production has been muddled, supplanted and ultimately made subservient to orthodox Western education forms and structures of colonial authorities. The global political economy of knowledge production has consigned indigenous knowledge to being regarded as traditional, unscientific and value-laden. Using philosophical logical reasoning and secondary data, the article critically engages with these issues, especially those that pertain to decolonisation of knowledge production in Africa in the age of globalisation. It provides an examination of pedagogical issues, especially teaching and learning methodologies. It also interrogates the knowledge of culture, mind, and self in knowledge production in Africa within the global context. In addition, it appraises research methodological platforms that inhibit Africanist solutions with global applicability. This is with a view to suggesting interventions that demonstrate the applicability of alternative frameworks of knowledge production in Africa.